Performance of Gas Induction in a Dual – Impeller Agitated Bioreactor - Mohammed, Alaa K.; Hussen, Hassanin Ali; Abid Al-Rassul, Safa (Al-Khwarizmi Engineering Journal, 2008)
The rate of gas induction was measured in gas-inducing type mechanically agitated contactors provided with two impellers. A reactor of 0.5 m i.d. was used with a working capacity of 60 liters of liquid. Tap water was used as the liquid phase, and air was used as the gas phase. The bioreactor mixing system consists of two equal diameter stirrers; the top impeller is shrouded-disk/curved-blade turbine with six evacuated bending blades, while the bottom impeller was disk turbine. The impeller speed was varied in the range of 50 to 800 rpm. The ratio of impeller diameter to tank diameter (D/T) and the submergence (S) of upper impeller from the top were varied. The effects of clearance of lower impeller from the tank bottom (C2) and the impeller spacing (C3, distance between the two impellers) were also varied over a wide range.  Rate of gas induction (Q) was measured for all these combinations. It was found that the rate of gas induction increases with both decreasing in submergence and increasing in the stirrer diameter. While it decreases with both increasing the impeller spacing and the clearance from the bottom.